Examining Growth Among College Students With Intellectual and Developmental Disability: A Longitudinal Study. Issue 2 (March 2021) - Lee, Chung Eun; Day, Tammy Lynn; Carter, Erik William; Taylor, Julie Lounds
Inclusive postsecondary education programs for adults with intellectual and developmental disabilities (IDD) are proliferating across the United States. Although college can be a formative time for any student, there has been limited research on the growth that college students with IDD may experience during their time on campus. We address this gap by using a longitudinal design to examine the adaptive behavior, self-determination, executive functioning, and social skills of college students with IDD across three points in time—upon initial entry into the program, at the end of their first year, and at the end of their second year. Analyses suggested significant improvements in adaptive behavior and self-determination across the first year of the program. We offer recommendations for research and practice aimed at documenting and promoting growth for students with IDD throughout their collegiate experience.